2020
DOI: 10.1002/cbin.11375
|View full text |Cite
|
Sign up to set email alerts
|

TMEM98 mRNA promotes proliferation and invasion of gastric cells by directly interacting with NF90 protein

Abstract: Transmembrane protein 98 (TMEM98) is a recently discovered gene, the inhibition of which has preliminarily been demonstrated to inhibit progression of several solid cancers in vitro. However, its involvement in tumorigenesis of gastric cancer (GC) has not been reported. Here, we aimed to explore the expression of TMEM98 in GC tissues and cell lines and to determine the role of TMEM98 in GC cell proliferation and invasion. TMEM98 was significantly upregulated in GC tissues, which was associated with low surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, TMEM98 was overexpressed in hepatocellular carcinoma and was significantly associated with advanced stage and poor prognosis [16]. In those with cervical adenocarcinoma [17], lung cancer [18], gastric cancer [19], and head and neck carcinoma [20], TMEM98 was also overexpressed in tumors compared to the normal tissues. In the TNMplot database, there were also significant differences in the expression of TMEM98 in different tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TMEM98 was overexpressed in hepatocellular carcinoma and was significantly associated with advanced stage and poor prognosis [16]. In those with cervical adenocarcinoma [17], lung cancer [18], gastric cancer [19], and head and neck carcinoma [20], TMEM98 was also overexpressed in tumors compared to the normal tissues. In the TNMplot database, there were also significant differences in the expression of TMEM98 in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [20] also found that down-regulation of TMEM98 represses prolif-eration ability and migration ability of head neck cancer cells. In gastric cancer, Ao et al [19] showed that cell proliferation and invasion were promoted by upregulation of TMEM98 mRNA. In our study, we found the exact opposite function by si-TMEM98 in OC.…”
Section: Discussionmentioning
confidence: 99%
“…In the MKN-45 and SGC-790 cell lines, the expression of TMEM98 was reduced by a siRNA, and this led to a significant decrease in cell proliferation and invasion, in a dose-dependent manner of the siRNA. The overexpression of TMEM98 with a recombinant protein in MKN-45 and SGC-7901 cells showed that the effect on cell proliferation and invasion is mediated by the TMEM98 mRNA and not by mature protein since protein levels increased, however, without effect on cell viability and invasion ( 54 ). Computer analysis identified the TMEM98 mRNA target protein as the RNA-binding protein nuclear factor 90 (NF90) to which TMEM98 mRNA binds through an 8-nucleotide motif, but the underlying mechanism of this binding remains unclear, but, whether the cancer-promoting effect through TMEM98 mRNA ( 54 ).…”
Section: Tmem Proteins Promote Cell Proliferation Migration and Invas...mentioning
confidence: 99%
“…Several reports have shown that some TMEM proteins have a specific role as oncogenes by promoting different processes in tumor cells as proliferation cell, migration, intravasation/extravasation, metastasis and modulation of the immune response ( 25 , 91 ). For example, in glioblastoma cells TMEM45A promoting cell proliferation, migration, and invasion ( 27 ) and TMEM98 in gastric cancer ( 54 ), among others. Some TMEM proteins have also been reported to favor epithelial-mesenchymal transition (EMT), such as TMEM45A in colorectal cancer ( 28 ).…”
Section: Introductionmentioning
confidence: 99%